GLP-1-Induced AMPK Activation Inhibits PARP-1 and Promotes LXR-Mediated ABCA1 Expression to Protect Pancreatic β-Cells Against Cholesterol-Induced Toxicity Through Cholesterol Efflux - Li, Rao; Sun, Xulong; Li, Pengzhou; Li, Weizheng; Zhao, Lei; Zhu, Liyong; Zhu, Shaihong (Frontiers in Cell and Developmental Biology, 2021)
T2DM (Type 2 diabetes) is a complex, chronic disease characterized as insulin resistance and islet β-cell dysfunction. Bariatric surgeries such as Roux-en-Y gastric bypass (RYGB) surgery and laparoscopic sleeve gastrectomy (LSG) have become part of a critical treatment regimen in the treatment of obesity and T2DM. Moreover, GLP-1 increase following bariatric surgery has been regarded as a significant event in bariatric surgery-induced remission of T2DM. In this study, a high concentration cholesterol-induced lipotoxicity was observed in INS-1 cells, including inhibited cell viability and insulin secretion. Enhanced cell apoptosis and inhibited cholesterol efflux from INS-1 cells; meanwhile, ABCA1 protein level was decreased by cholesterol stimulation. Cholesterol-induced toxicity and ABCA1 downregulation were attenuated by GLP-1 agonist EX-4. GLP-1 induced AMPK phosphorylation during the protection against cholesterol-induced toxicity. Under cholesterol stimulation, GLP-1-induced AMPK activation inhibited PARP-1 activity, therefore attenuating cholesterol-induced toxicity in INS-1 cells. In INS-1 cells, PARP-1 directly interacted with LXR, leading to the poly(ADP-ribosyl)ation of LXRα and downregulation of LXR-mediated ABCA1 expression. In the STZ-induced T2DM model in rats, RYGB surgery or EX-4 treatment improved the glucose metabolism and lipid metabolism in rats through GLP-1 inhibition of PARP-1 activity. In conclusion, GLP-1 inhibits PARP-1 to protect islet β cell function against cholesterol-induced toxicity in vitro and in vivo through enhancing cholesterol efflux. GLP-1-induced AMPK and LXR-mediated ABCA1 expression are involved in GLP-1 protective effects.